2015
DOI: 10.1111/1750-3841.13104
|View full text |Cite
|
Sign up to set email alerts
|

Antilisterial Peptides Released by Enzymatic Hydrolysis from Grass Carp Proteins and Activity on Controlling L. monocytogenes Inoculated in Surimi Noodle

Abstract: The results of this study indicated that antilisterial peptides generated via neutrase from grass carp proteins can efficiently inhibit the growth of L. monocytogenes in surimi noodle, which was useful as natural preservatives for storage and distribution of meat based products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Hence, F1 depicted multiple cell targets in the killing of E. coli. Xiao and Niu (2015) verified the production of the antilisterial peptides released by enzymatic hydrolysis from grass carp proteins and then evaluated their antilisterial activity against L. monocytogenes inoculated in surimi noodle for storage at 4 and 25 °C up to 20 days. The results indicated that antilisterial peptides produced by enzymatic hydrolysis from grass carp proteins can inhibit the growth of L. monocytogenes in surimi noodle, which was useful as natural food preservatives of meat products.…”
Section: Resultsmentioning
confidence: 98%
“…Hence, F1 depicted multiple cell targets in the killing of E. coli. Xiao and Niu (2015) verified the production of the antilisterial peptides released by enzymatic hydrolysis from grass carp proteins and then evaluated their antilisterial activity against L. monocytogenes inoculated in surimi noodle for storage at 4 and 25 °C up to 20 days. The results indicated that antilisterial peptides produced by enzymatic hydrolysis from grass carp proteins can inhibit the growth of L. monocytogenes in surimi noodle, which was useful as natural food preservatives of meat products.…”
Section: Resultsmentioning
confidence: 98%
“…Its muscle and skin hydrolysates were reported to show angiotensin‐I converting enzyme (ACE) inhibition (Yi et al., 2016 ) and antioxidant activities (Chen et al., 2016 ). The antilisterial peptides derived from grass carp proteins can efficiently inhibit the growth of L. monocytogenes in surimi noodle (Xiao & Niu, 2015 ). Furthermore, a novel excellent ACE inhibitory peptide Val‐Ala‐Pro (Chen et al., 2012 ) and a potent antioxidant peptide Pro‐Ser‐Lys‐Tyr‐Glu‐Pro‐Phe‐Val (Zhao et al., 2008 ) were isolated from the grass carp protein hydrolysates prepared with alcalase.…”
Section: Introductionmentioning
confidence: 99%
“…The antilisterial peptides derived from grass carp proteins can efficiently inhibit the growth of L. monocytogenes in surimi noodle (Xiao & Niu, 2015). Furthermore, a novel excellent ACE inhibitory peptide Val-Ala-Pro (Chen et al, 2012) and a potent antioxidant peptide Pro-Ser-Lys-Tyr-Glu-Pro-Phe-Val (Zhao et al, 2008) were isolated from the grass carp protein hydrolysates prepared with alcalase.…”
mentioning
confidence: 99%
“…38 Xiao et al hydrolyzed grass carp with neutral protease, and the obtained grass carp protein hydrolysates effectively inhibited the growth of Listeria monocytogenes in surimi noodles, which could be used as a natural preservative for the storage and distribution of meat products. 39 A novel antibacterial peptide LCH4 was found in the hemoglobin sequence of Larimichthys crocea. It reduced the biofilm formation rate of Staphylococcus aureus and Vibrio parahemolyticus and had a strong inhibitory effect on the growth of pathogenic bacteria in soy sauce, and no cytotoxic effect on normal human liver cells, which made LCH4 a good application prospect as a food preservative.…”
Section: Gelationmentioning
confidence: 99%